2022
DOI: 10.1007/s40273-022-01133-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Issues of Valuing Child and Adolescent Health States Using a Mixed Sample of Adolescents and Adults

Abstract: for comments on a previous draft. We would also like to thank Donna Davis and Liz Mclintock for project management and formatting of the report, and Ruth Wong for undertaking the literature searches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…A recent study has shown, for example, that respondents are less willing to trade lifeyears on behalf of others [22]. A promising new approach is to elicit preferences from a mixed sample of adults and adolescents [24]. There are numerous strengths of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown, for example, that respondents are less willing to trade lifeyears on behalf of others [22]. A promising new approach is to elicit preferences from a mixed sample of adults and adolescents [24]. There are numerous strengths of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Arguments supporting this approach include coherence with the population used to generate value sets for adult measures; adults bear the costs of healthcare through health insurance; adults' capacity of decision making (both in general and about health) and legal rights to participate in certain activities (e.g. voting, signing a contract, getting married); ethical difficulties around the acceptability of valuation exercises involving the concept of death for young populations; and matters of understanding and cognitive burden associated with the task in adolescents or children [24][25][26][27]. In Hungary, no value set exists for the EQ-5D-Y-3L or any other youth-specific health status measure.…”
Section: Introductionmentioning
confidence: 99%
“…However, for normative reasons, some relevant stakeholders (i.e., local end-users) may have priorities that extend beyond the alignment between the resulting value set and the observed cTTO values. There may be cases where alignment with the DCE data is prioritised, such as when mixed samples are sought [ 27 ]. For example, if adolescents complete the DCE and adults complete the cTTO, the use of linear mapping will ensure that adolescents’ preferences (in relation to the relative importance of dimensions) are fully represented in the value set.…”
Section: Discussionmentioning
confidence: 99%
“…However, the protocol was only considered to be a starting point, with further updates expected in future due to the various ongoing normative and methodological debates in the context of child health valuation [ 4 , 25 ]. These debates include, but are not limited to, the source of preference data [ 26 , 27 ], the perspective taken in the task [ 6 , 7 , 9 , 28 ], and the choice of valuation method [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence from the literature that adults think that adults and children have different coping abilities. For example, children and adolescents are thought to be more flexible and can adapt more easily to health challenges than can adults, in part because they will be able to get support from their parents/caregivers and society 29–32…”
Section: Introductionmentioning
confidence: 99%